STRATEGI KOMUNIKASI LEMBAGA AMIL ZAKAT NURUL FIKRI ZAKAT CENTER DALAM UPAYA PENGHIMPUNAN DANA UMAT DI KALIMANTAN TENGAH - Adi Cahyono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The management of zakat essentially covers the purposes and usefulness of communication. An informative, persuasive and entertained zakat message provides a person with the potential for zakah to believe it is an obligation. Furthermore, the sense of confidence that makes them stirred to practice and with pleasure and feel secure after the zakat fulfilled. The problems raised in this research are: 1) How is the communication strategy used by NF Zakat Center in collecting zakat in Central Kalimantan, then the next issue 2) How marketing activities conducted by NF Zakat Center, and 3) How NF Zakat Center utilize zakat to the mustahik. This type of research is a qualitative research conducted in two stages of preliminary research and advanced research. The data source of the researchers comes from a collection of NF Zakat Center archives. Data collection methods used were in-depth interviews, observation and documentation. Furthermore, data management techniques and data analysis is done to answer the questions.The results of this study indicate that the communication strategy implemented by NF Zakat Center in the effort to collect the funds of the people in the form of zakat, infaq and charity is through interpersonal communication in order to foster good relationship with muzakki, candidate muzakki and the mustahik. NF Zakat Center maximizes the collection efforts through online and online marketing activities by regularly to visit each others and utilizing social media channels. The programs and activities of empowerment in strategic and targeted areas have a positive impact in supporting the efforts of raising people's funds by the NF Zakat Center in Central Kalimantan. Keywords: Communication Strategics and Zakat